Microbes influence the biogeochemical and optical properties of maritime Antarctic snow. Issue 6 (17th June 2017) - Hodson, A. J.; Nowak, A.; Cook, J.; Sabacka, M.; Wharfe, E. S.; Pearce, D. A.; Convey, P.; Vieira, G.
Abstract: Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there. Key Points: Microbial activity in wet Antarctic snow is detectable from its organic and inorganic carbon contents and the CO2 of interstitial air Snow algae cause absorption of visible light and thus more melting due to carotenoid and chlorophyll pigment development Inland Antarctic glacial snowpacks have far less diverse microbial communities than coastal snowpacks